C9orf72’s Interaction with Rab GTPases—Modulation of Membrane Traffic and Autophagy - Tang, Bor L. (Frontiers in Cellular Neuroscience, 2016)
Hexanucleotide repeat expansion in an intron of Chromosome 9 open reading frame 72 (C9orf72) is the most common genetic cause of Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Dementia (FTD). While functional haploinsufficiency of C9orf72 resulting from the mutation may play a role in ALS/FTD, the actual cellular role of the protein has been unclear. Recent findings have now shown that C9orf72 physically and functionally interacts with multiple members of the Rab small GTPases family, consequently exerting important influences on cellular membrane traffic and the process of autophagy. Loss of C9orf72 impairs endocytosis in neuronal cell lines, and attenuated autophagosome formation. Interestingly, C9orf72 could influence autophagy both as part of a Guanine nucleotide exchange factor (GEF) complex, or as a Rab effector that facilitates transport of the Unc-51-like Autophagy Activating Kinase 1 (Ulk1) autophagy initiation complex. The cellular function of C9orf72 is discussed in the light of these recent findings